Intervensi Pekerjaan Sosial terhadap Perempuan Rawan Sosial Ekonomi dalam Meningkatkan Pemahaman Keluarga Berencana di BKKBN Provinsi Sumatera Utara - Andre Vandame Siregar; Mia Aulina Lubis (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to describe the process of social work intervention for Socioeconomically Vulnerable Women in improving family planning understanding at the National Population and Family Planning Board (BKKBN) of North Sumatra Province. This study employed a qualitative method with a case study approach. Data were collected through observation, interviews, and documentation during the implementation of social work practice. Case analysis utilized the Person-in-Environment (PIE) approach to understand the relationship between the individual's condition and their social environment, as well as the Strengths Perspective to identify the client's potentials and strengths. The assessment results revealed that the client had limited understanding of family planning programs, the benefits of contraceptive use, and the importance of family planning in supporting family welfare. Social work intervention was carried out through the stages of engagement, assessment, planning, intervention, evaluation, and termination. The intervention activities included information dissemination, counseling, education, and motivational reinforcement. The evaluation results indicated an improvement in the client's understanding of family planning and the emergence of greater awareness regarding the importance of family planning as an effort to enhance family quality of life. These findings demonstrate that social work interventions through a social casework approach contribute to helping clients improve their understanding and decision-making capacity related to family planning.